2002
DOI: 10.1557/proc-740-i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Mechanical Properties of Nanostructured Copper-304 Stainless Steel Multilayers Synthesized by Magnetron Sputtering

Abstract: Nanostructured Cu/304 stainless steel (SS) multilayers were prepared by magnetron sputtering at room temperature. 304SS has a face-centered cubic (fcc) structure in bulk. However, in the Cu/304SS multilayers, the SS layers exhibited fcc structure for layer thickness of less than or equal to 5 nm. For 304SS layer thickness larger than 5nm, bcc 304SS grains were observed to grow on top of the initial z 5 nm of fcc SS. The maximum hardness of Cu/304SS multilayers was z 5.5 GPa (factor of two enhancement compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In recent years, NT metals (Cu and Ag) have been successfully synthesized with several techniques such as magnetron sputtering and pulsed electrodeposition methods. [3,9,10,11] Compared with coarse-grained and nanocrystalline metals, the NT structures exhibit outstanding thermal stability and enhanced mechanical strength due to the nano-scaled twin boundary spacings. [5,9,[12][13][14] Lu et al reported ultra-high strength for NT Cu, [1] while Anderoglu et al have shown extremely high hardness with the remarkable thermal stability of sputter-deposited NT Cu film by using the ex situ annealing and indentation experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] In recent years, NT metals (Cu and Ag) have been successfully synthesized with several techniques such as magnetron sputtering and pulsed electrodeposition methods. [3,9,10,11] Compared with coarse-grained and nanocrystalline metals, the NT structures exhibit outstanding thermal stability and enhanced mechanical strength due to the nano-scaled twin boundary spacings. [5,9,[12][13][14] Lu et al reported ultra-high strength for NT Cu, [1] while Anderoglu et al have shown extremely high hardness with the remarkable thermal stability of sputter-deposited NT Cu film by using the ex situ annealing and indentation experiments.…”
mentioning
confidence: 99%
“…[3,9,10,11] Compared with coarse-grained and nanocrystalline metals, the NT structures exhibit outstanding thermal stability and enhanced mechanical strength due to the nano-scaled twin boundary spacings. [5,9,[12][13][14] Lu et al reported ultra-high strength for NT Cu, [1] while Anderoglu et al have shown extremely high hardness with the remarkable thermal stability of sputter-deposited NT Cu film by using the ex situ annealing and indentation experiments. [15] Twin boundaries in face-centered cubic (fcc) metal can also function as barriers to dislocation climb due to their thermal stability at elevated temperatures.…”
mentioning
confidence: 99%